Mastering IBM WebSphere portal - Ben-Natan, Ron (Wiley, 2004)
Maximize on the power of WebSphere Portal to build and deploy portalsIf you use, develop, manage, or administer WebSphere applications, you are probably already building or managing Web portals-or well on your way to doing so. With this comprehensive book, you'll discover how these portals bring together important functions such as integration, presentation, organization, and customizations-functions needed in every complex application environment. The unparalleled author team of experts offers you in-depth insight on mastering the complex aspects of WebSphere Portal, walking you throu.